Genetic characterization of a mammalian protein-protein interaction domain by using a yeast reverse two-hybrid system. - Vidal, M (1996)
Many biological processes rely upon protein-protein interactions. Hence, detailed analysis of these interactions is critical for their understanding. Due to the complexities involved, genetic approaches are often needed. In yeast and phage, genetic characterizations of protein complexes are possible. However, in multicellular organisms, such characterizations are limited by the lack of powerful selection systems. Herein we describe genetic selections that allow single amino acid changes that disrupt protein-protein interactions to be selected from large libraries of randomly generated mutant alleles. The strategy, based on a yeast reverse two-hybrid system, involves a first-step negative selection for mutations that affect interaction, followed by a second-step positive selection for a subset of these mutations that maintain expression of full-length protein (two-step selection). We have selected such mutations in the transcription factor E2F1 that affect its ability to heterodimerize with DP1. The mutations obtained identified a putative helix in the marked box, a region conserved among E2F family members, as an important determinant for interaction. This two-step selection procedure can be used to characterize any interaction domain that can be tested in the two-hybrid system.